Critical Mathematics Education and its contribution to the formation of the historical subject and its emancipation - Magalhães, Benedita Neire Almeida de; Darsie, Martha Maria Pontin (Seven Editora, 2023)
This article is the result of bibliographical research and literature review directed to Mathematics Education and Citizenship, from critical theory, but without losing the influences of analysis of other currents of thoughts that give possibilities for a dialogue between epistemologos. Thus, it is a brief theoretical reflection, from the thought of Theodor W. Adorno and together with other theoretical references such as: Paulo Freire, Bauman, Morin, and the Danish professor Ole Skovsmose. It is also noteworthy that these authors consider that, from pedagogical practices that stimulate criticality and dialogue, the subject’s education will be active, reflective, critical, favoring the strengthening of citizenship. It is in this context that the present work aims to focus and bring the theoretical foundation to the debate of education that aims to provide the creation of a critical and democratic environment inside and outside the classroom. Finally, it is concluded that it is of paramount importance to look at mathematics, which should highlight and add practices of reflection and dialogue, in order to provide the creation of a critical and liberating environment. DOI:https://doi.org/10.56238/ptoketheeducati-016